2008
DOI: 10.3892/or.19.4.865
|View full text |Cite
|
Sign up to set email alerts
|

BIGH3 is overexpressed in clear cell renal cell carcinoma

Abstract: To identify new target marker genes in renal cell carcinoma (RCC), we compared the gene expression profiles of clear cell RCC (cc-RCC) and normal kidney tissue using serial analysis of gene expression. Our results revealed that the transforming growth factor ß induced 68 kDa protein (TGF-ßI: ß ig-h3 (BIGH3), plasminogen activator inhibitor-1 (PAI-1) and transforming growth factor ß1 (TGF-ß1) genes are upregulated in cc-RCC. To further assess the role of BIGH3 in RCC, we investigated the mRNA expression levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…We speculate that TGFBI may have a dual role, promoting the proliferation of osteoblast and chondrocyte precursors and inhibiting the differentiation of mature osteoblasts, with the net result of increasing bone mass and bone size. Previous findings in other studies support a role of TGFBI in cell proliferation: TGFBI is highly expressed in the growth area and cancer cells and involved in tumor invasion and metastasis [13,25,26]. A gene-expression analysis also indicated the biphasic nature of TGFBI in the fact that the mRNA and protein of TGFBI were highly expressed in the early stages of chondrocyte differentiation but decreased in the later stages [47].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…We speculate that TGFBI may have a dual role, promoting the proliferation of osteoblast and chondrocyte precursors and inhibiting the differentiation of mature osteoblasts, with the net result of increasing bone mass and bone size. Previous findings in other studies support a role of TGFBI in cell proliferation: TGFBI is highly expressed in the growth area and cancer cells and involved in tumor invasion and metastasis [13,25,26]. A gene-expression analysis also indicated the biphasic nature of TGFBI in the fact that the mRNA and protein of TGFBI were highly expressed in the early stages of chondrocyte differentiation but decreased in the later stages [47].…”
Section: Discussionmentioning
confidence: 68%
“…Although it is present in a wide range of tissues, TGFBI is highly expressed in bone, cartilage, cornea, kidney, and skin [8,21]. It is an important molecule studied for cancers [8,[22][23][24][25][26][27][28][29][30], corneal dystrophies [8,31,32], and wound healing [15,[33][34][35]. A few in vitro studies related to bone metabolism have found that TGFBI has a positive effect on the adhesion and migration of osteoblasts and a negative effect on the differentiation and mineralization of osteoblasts as well as hypertrophic chondrocytes [17,18,36,37].…”
mentioning
confidence: 99%
“…The cancer microarray database ONCOMINE [24] revealed other microarray gene-expression studies in which TGFBI was also reported as one of the most significant genes upregulated in RCC tumors, when compared with adjacent normal kidney tissue. Recently, it has been shown that there was an association between TGFBI expression and the von Hippel Lindau (VHL) [25]. TGFBI is important for the adhesion, the migration, and the invading ability of RCC cells especially for cell lines with inactive VHL [23].…”
Section: Discussionmentioning
confidence: 99%
“…Over expression of Poly [ADP-ribose] polymerase 1 was found to be significantly down regulated in Gef-SD groups (46). BIGH3 promotes adhesion and invasion potential of cancer cells (47) and its expression was also significantly down regulated in Gef-SD treated animals.…”
Section: Discussionmentioning
confidence: 99%